Pharmacotherapeutic Management of Dementia Across Settings of Care. Issue 5 (16th April 2013) - Rattinger, Gail B.; Burcu, Mehmet; Dutcher, Sarah K.; Chhabra, Pankdeep T.; Rosenberg, Paul B.; Simoni‐Wastila, Linda; Franey, Christine S.; Walker, Loreen D.; Zuckerman, Ilene H.
<x xml:space="preserve">Abstract</x> Objectives To describe population‐based use of cognitive‐enhancing and psychopharmacological medications across care settings in Medicare beneficiaries with dementia. Design One‐year (2008) cross‐sectional study. Setting Medicare administrative claims from a 5% random sample. Participants Medicare beneficiaries with dementia aged 65 and older with continuous Medicare Parts A, B, and D coverage and alive throughout 2008. To ascertain dementia, one or more medical claims with a dementia International Classification of Diseases, Ninth Revision, Clinical Modification code was required before 2008, and an additional claim was required in 2008 to confirm active disease. Measurements Use of medications commonly prescribed in managing dementia (cognitive enhancers, antidepressants, antipsychotics, and mood stabilizers) was assessed using three measures: annual prevalence of use, consistency of use, and count of psychopharmacological medication classes. Care setting was determined using the number of months of nursing home (NH) residency: no NH (0 months), partial NH (1–11 months), and full NH (12 months). Results Community‐dwellers represented 41.3% of the cohort, whereas 42.4% and 16.3% resided partially and fully in a NH, respectively. Annual prevalence of use was 57.1% for cognitive enhancers, 56.4% for antidepressants, 34.0% for antipsychotics, and 8.8% for mood stabilizers. Cognitive enhancer use was significantly lower in those with any NH stay (partial NH vs no NH, adjusted prevalence ratio (APR) = 0.84, 99% confidence interval (CI) = 0.83–0.86; full NH vs no NH, APR = 0.83, 99% CI = 0.81–0.85). In contrast, those with any NH residence had significantly higher use of all psychopharmacological medication classes than community‐dwellers. More than half the cohort had consistent medication regimens during 2008 (64.8%). The number of psychopharmacological medication classes used increased with increasing NH stay duration. Conclusion This population‐based study documents significant differences in medication use for managing dementia between care settings and substantial use of psychopharmacological medications in older adults with dementia.